Analisis Pengaruh Pendapatan dan Pengetahuan terhadap Minat Berinvestasi di Pasar Modal Syariah pada Pedagang Grosir Pasar Aur Blok A,B & C Kota Bukittinggi - Cindy Aura Briliana; Amsah Hendri Doni (Universitas 17 Agustus 1945 Semarang, 2024)
This research is motivated by the fact that Income and Knowledge are among the factors influencing Investment Interest, yet most traders have a relatively stable income from their trading businesses. The objective of this research is to determine and analyze the simultaneous and partial influence of income and knowledge on investment interest in the sharia capital market among wholesale traders in the Aur Market blocks A, B, and C in the city of Bukittinggi. This study is a field research using a descriptive quantitative method. The population in this study consists of 868 traders, and a sample of 90 traders is drawn to serve as respondents using a sampling method. The selection of traders is done randomly in the wholesale area of Aur Market blocks A, B, and C. Based on the data processing and analysis conducted, the result of the simple linear regression equation Y = 11,750 + 0.026 X1 + 0.449 X2 is obtained. It can be stated that Income (X1) has a positive but not significant influence, while Knowledge (X2) has a positive and significant influence on investment interest (Y) among wholesale traders in Aur Market blocks A, B, and C in the city of Bukittinggi. The result of the income value 0,202 < , meaning is accepted and is rejected, the knowledge value 5,241 > , meaning is rejected and is accepted. Simultaneously, the result of the income and knowledge 15,885 > , meaning is rejected and is accepted. The coefficient of determination ( ) result is 0.267 or 26.7%, which means that 26.7% of the investment interest is influenced by income and knowledge, while the remaining 73.3% is influenced by other variables not examined in this study. The theoretical independent variables are lifestyle, personality, and promotion.